Detecting charging state of ultra-fine particles: instrumental development and ambient measurements - L. Laakso; S. Gagné; T. Petäjä; A. Hirsikko; P. P. Aalto; M. Kulmala; V.-M. Kerminen (Atmospheric Chemistry and Physics, 2007)
The importance of ion-induced nucleation in the lower atmosphere has been discussed for a long time. In this article we describe a new instrumental setup – Ion-DMPS – which can be used to detect contribution of ion-induced nucleation on atmospheric new particle formation events. The device measures positively and negatively charged particles with and without a bipolar charger. The ratio between "charger off" to "charger on" describes the charging state of aerosol particle population with respect to equilibrium. Values above one represent more charges than in an equilibrium (overcharged state), and values below unity stand for undercharged situation, when there is less charges in the particles than in the equilibrium. We performed several laboratory experiments to test the operation of the instrument. After the laboratory tests, we used the device to observe particle size distributions during atmospheric new particle formation in a boreal forest. We found that some of the events were clearly dominated by neutral nucleation but in some cases also ion-induced nucleation contributed to the new particle formation. We also found that negative and positive ions (charged particles) behaved in a different manner, days with negative overcharging were more frequent than days with positive overcharging.